Moc Jezusowego słowa w dziele Łukaszowym - Mielcarek, Krzysztof (Verbum vitae, 2008)
The article gives a short panorama and two major glimpses of the Lukan theology of the word. The first one touches upon the phrase hoi logoi tes charitos which belongs to the very vocabulary of the third evangelist (Lk 4,22; Ac 14,3; 20,24.32). According to Luke words of the Lord contain grace, that is a supematural kind of impact, which is at work when the words are proclaimed. The parable of the seed (Lk 8,4-21) is another testimony of Lukan theology. The pericope is full of specifically Lukan words and phrases that present God's word as an almost autonomous reality that is able to bear fruit in the life of man. Through the activity of the Holy Spirit it also has a strong church-building power (Lk 8,21; cf. Dz 2,2-4.33.41n.).